2014
DOI: 10.1080/15732479.2013.862727
|View full text |Cite
|
Sign up to set email alerts
|

Measuring and modelling the thermal performance of the Tamar Suspension Bridge using a wireless sensor network

Abstract: Suspension Bridge using a wireless sensor networkA study on the thermal performance of the Tamar Suspension Bridge deck in Plymouth, U.K., is presented in this paper. Ambient air, suspension cable, deck and truss temperatures were acquired using a wired sensor system. Deck extension data were acquired using a two-hop wireless sensor network. Empirical models relating the deck extension to various combinations of temperatures were derived and compared. The most accurate model, which used all the four temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…Case studies on SHM [4][5][6][7], specially focused on damage identification and structural safety maintenance, for application on large infrastructures as well as on residential and commercial buildings, have become increasingly narrated in the literature. Examples of the decentralized systems and advances on the development of sensors are frequently introduced in the structural monitoring area [8][9][10].…”
Section: Importance Of Shm For Structural Safety Maintenancementioning
confidence: 99%
“…Case studies on SHM [4][5][6][7], specially focused on damage identification and structural safety maintenance, for application on large infrastructures as well as on residential and commercial buildings, have become increasingly narrated in the literature. Examples of the decentralized systems and advances on the development of sensors are frequently introduced in the structural monitoring area [8][9][10].…”
Section: Importance Of Shm For Structural Safety Maintenancementioning
confidence: 99%
“…Another point stems from measurements of temperature and extension data in the bearing arrangement, obtained in July 2010, which revealed that the gap extension against temperature is perfectly adjusted to a linear relation, and therefore, does not indicate any relevant frictional force (see Fig. 15 of Battista et al [14] for clarification). The bearings and the string gauge sensor used for such assessment are shown in Fig.…”
Section: The Tamar Bridge Reference and Current State Datasetsmentioning
confidence: 99%
“…The major part of the cumulative sliding displacement is obtained from the vehicle‐induced dynamic displacement. In general, the displacement of bridge bearings is monitored by the displacement sensors with a frequency as small as 1 Hz or smaller . The low‐frequency displacement sensors cannot record the high‐frequency bearing displacement information.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the displacement of bridge bearings is monitored by the displacement sensors with a frequency as small as 1 Hz or smaller. [16][17][18][19][20] The low-frequency displacement sensors cannot record the high-frequency bearing displacement information. Additionally, the main girder will vibrate with various modes, including relatively high-frequency modes, for practical bridges subject to vehicle/wind loads.…”
Section: Introductionmentioning
confidence: 99%